If these walls could talk [large type] - Crownover, James D. (Wheeler Publishing large print western, 2019)
" Can the walls of an abandoned house absolve a man accused of a thirty-year-old murder? Not before Silent Cooper and Dempsy Nealy battle Apache thieves, Pancho's Villistas, marauding outlaws, and El Tigre of the Playas Valley. The loss of a letter beneath the ruins of a famous Arizona ranch house thirty years ago led to an untimely marriage for Dempsy's Aunt Cindy, who now runs three ranches with an iron will and a shotgun loaded with buckshot. No man stands in her way--for long. Dempsy dreams of a ghostly visitor in the desert, or was it a dream? The rock house of the Smuggler Hills seems to be an impregnable fortress until a small creature descends the chimney. A cemetery reveals a scandalous secret. "--